UNFINISHED STUDENT ANSWER IN PISA MATHEMATICS CONTEXTUAL PROBLEM - Moch. Lutfianto; Zulkardi Zulkardi; Yusuf Hartono (Journal on Mathematics Education, 2013)
Solving mathematics contextual problems is one way that can be used to enable students to have the skills needed to live in the 21st century. Completion contextual problem requires a series of steps in order to properly answer the questions that are asked. The purpose of this study was to determine the steps performed students in solving contextual mathematics problem. The results showed that 75% students can not solve contextual mathematics problems precisely (unfinished). Students stop and feel that it was completed when they are able to solve problems mathematically, but mathematical solution has not answered the requested context.